Estudos de contaminação bacteriológica e de matéria orgânica nas águas de aquíferos livres (poços escavados) e de águas superficiais de rios e igarapés - Souza, Francimara Costa de (Museu Paraense Emílio Goeldi, 2023)
Belém is supplied mainly by surface water from the Guamá River and the Bolonha and Água Preta lakes. The water from the rivers used for treatment must have characteristics that conform to established norms regarding the presence of fecal and total coliforms, biochemical oxygen demand (BOD) and chemical oxygen demand (COD). The Guamá River presented results of fecal and total coliforms of 11X105 MPN/100ml, value out of the established standards (CONAMA standard 4x 103 MP/100ml for fecal coliforms and 2x 104 MPN/100ml for total coliforms), while the values of BOD (average 6 mg/l of O2 ) and COD (20 mg/I O2 ) are within the standards (standard for BOD 10mg/1 of O2 , The landfills produce a leachate, the leachate, which is usually treated or stabilized before being released into the environment, with control characteristics, evaluated by BOD and COD. The efficiency of the stabilization pond and filters at the Aurá landfill is not satisfactory. The BOD and COD of the effluents from these lagoons are high reaching BOD of 1700 mg/I O2 (SESAN report) and for COD 784 mg/I O2 (measured values). This COD is compared with those found for untreated petrochemical industry effluents. The effluents reach the natural waters of the rivers with high levels of 02, degrading the aquatic environment and limiting the life of several species. The monitoring of effluents and the improvement of slurry stabilization conditions can minimize this situation.